FUNGAL INFECTIONS IN NEONATOLOGY - MODERN VIEW ON THE PROBLEM - T. Znamenska; T. Kurilina (Bukovynian State Medical University, 2019)
Modern views on diagnostics, treatment and prophylactics of mycosis in newborns which are proposed to lay in basis of clinical protocol are presented.